The Role of the Cooperative Script Method in Developing Self-Confidence and Public Speaking Skills Among Madrasah Ibtidaiyyah Student - Isa Anshori; M. Rofiqul Majid; Sufatul Fitria; Ghazwu Fikril Haq (Jurnal Pendidikan Islam, 2024)
The Cooperative Script Method (CSM) has gained prominence as an instructional approach that enhances key student skills, including self-confidence and public speaking abilities. This study aimed to investigate the impact of CSM on students' self-confidence and public speaking skills. The research was conducted at Madrasah Ibtidaiyah Al-Anwar Sarang using a quantitative approach, involving 37 purposively selected fifth-grade students. Data were collected through questionnaires, complemented by in-depth observations, and analyzed using linear regression and the Sobel test. The results indicated that CSM significantly enhances students' self-confidence (p